The influence of Americanization on savings behavior and practices among Saudi Arabian families immigrants in the United States - Alkhiary, Adnan Mohammed (Kansas State University, 2015)
This investigation sought to examine the role of acculturation and generational theory and influenced social and cultural practices among Saudi Arabian students who were currently residing in the United States. Theoretically, it sought to answers questions that help determine how Americanization—the adaptation and acculturation of a visiting culture to absorb and incorporate the host culture into their lives, customs, and social practices, and in this case savings behavior. A comprehensive model was developed to test the idea that living in America can and does have an influence on social and cultural practices. What was of interest in this study was whether or not these same influences could have an impact on particular cultural practices, in this case how people felt about, reacted to, and addressed the concept of savings—the stockpiling of funds for future needs. Information was gathered from a sample of over 500 Saudi Arabian students living in the United States. The model as structured was tested using SEM analytic techniques in an effort to fully explore and expose the nuanced and subtle differences among the respondents. The concept of savings behavior being influenced by Americanization as originally discussed was not substantiated by the model even though some of the indicators were within expected parameters (χ² = 217.241, p < .001; CFI = 0.839, TLI = 0.732, RMSEA = 0.034). Despite the general problems the overall model revealed that at least 17% of what was termed as savings behavior could be explained by the model. The study still retained its value because it has made inroads into an area that has not yet been explored. Future investigations should take care to find better ways to incorporate some of the cultural elements of savings behavior directly into the instrument based on the perspective of their test populations rather than assume value in and use instruments tested and normed with US samples.
Keywords: Acculturation and cultural practices; Social and social practices; Americanization; Savings behavior theory; Savings behavior model; Family finance; Economics, Finance (0508); Home Economics (0386); Individual & Family Studies (0628); Social Research (0344)